Authentic Assessment through Analytic Teams Technique in Empowering Students’ Speaking Skills - Haris Hamdani; Ninuk Lustyantie; Fathiaty Murtadho (Edulitics (Education, Literature, and Linguistics) Journal, 2024)
Learning in higher education is fundamentally an activity which is conducted in a planned and structured manner to create an environment and provide services that enable students to learn effectively. The major duty of lecturers is to organize and implement learning, as well as conduct an assessment of each content that has been taught. For that reason, this research is trying to investigate: (1) authentic assessments through analytic team technique implemented in English learning and teaching, (2) the types of authentic assessment used, (3) the teachers’ perception of the implementation of authentic assessment through analytic teams technique in empowering students’ speaking skills. This study applied qualitative design to apprehend the implementation of authentic assessment through analytic teams technique. Observation, interview, and documentation were conducted to get the data. The results showed that the authentic assessment through the analytic team's technique applied in the English lecturer class of Universitas Bhayangkara Jakarta Raya at the Communication Science Department is level good. Both lectures implemented authentic assessments through analytic team technique in the learning and teaching process. The types of authentic assessments were performance assessment, observation and question, presentation and discussion, experiments, storytelling, and self-assessment. Furthermore, the lecturers’ perception of the implementation of authentic assessment through the analytic teams technique can empower students’ speaking skills. This research implies that educators can enhance students’ speaking skills using authentic assessments through the analytic teams technique to better outcomes in students' speaking skills, and to take ownership of their learning.